Hubungan Antara Partisipasi dengan Kepuasan Pemakai Dalam Pengembangan Sistem Berbasis Komputer: Suatu Tinjauan Dua Faktor Kontijensi - Grahita Chandrarin; NUR INDRIANTORO (Journal of Indonesian Economy and Business (JIEB), 1997)
User participation has been widely touted by the MIS community as ameans to improve user satisfaction within systems development This claim, however, has not been consistently substantiated in the empirical literature. In seeking to explain such equivocal results, the effects of two contingency factorstask complexity and system complexity-on the relationship between user participation and user satisfaction were investigated. As suggested in the literature, this research tests hypotheses that these specific contingency factors should aid in identifying situations where user participation would have a strongrelationship with satisfaction. Analysis of 135 respondents in different organizations indicated that user participation has direct relationship with user satisfaction. In addition, the two contingency factors task complexity and system complexity prove to be not pure moderator. Task complexity was shown to be independent predictor of user satisfaction, and system complexity to be quasi moderator of relationship betweenuser participation and user satisfaction The results help explain the relationship between user participation and user satisfaction by suggesting the nature of the relationship under different sets of conditions. In the implications are relevant to systems developers and toacademicians seeking to explain how, when, why, and where user participation is needed.